Hotterdam: mapping the Rotterdam urban heat island - van der Hoeven, Frank; Wandl, Alexander (project baikal, 2015)
The urban heat island is considered to be one of the contemporary health aspects that cities urgently need to respond to. The Hotterdam research project addresses the Rotterdam urban heat island, in order to explain the links between the health of the city’s population and the features of its built environment that make it more or rather less warm. The work resulted in two heat maps that make the city of Rotterdam and its inhabitants more aware of and less susceptible to the health effects of heat waves. The insights into the urban heat island that were gained in this project are relevant for other cities in Holland (Amsterdam, The Hague) and abroad.
Keywords: urban heat island; ground heat flux; urban design; spatial planning; built environment; climate adaptation; Rotterdam